How does social evaluation influence Hot and Cool inhibitory control in adolescence? - Lison Bouhours (Public Library of Science (PLoS), 2021)
The aim of the present study is to examine whether in Hot, i.e., affectively charged contexts, or cool, i.e., affectively neutral contexts, inhibitory control capacity increases or decreases under social evaluation in adolescents and adults. In two experiments, adolescents and young adults completed two Stroop-like tasks under either a social evaluation condition or an alone condition. The social evaluation condition comprised the presence of a peer (Experiment 1) or an expert (Experiment 2) playing the role of an evaluator, while under the alone condition, the task was performed alone. In the Cool Stroop task, participants had to refrain from reading color names to identify the ink color in which the words were printed. In the Hot Stroop task, participants had to determine the emotional expression conveyed by faces from the NimStim database while ignoring the emotion word displayed beneath. The results were similar in both experiments. In adolescents, social evaluation by a peer (Experiment 1) or by an expert (Experience 2) facilitated Hot but not cool inhibitory control. In adults, social evaluation had no effect on Hot or cool inhibitory control. The present findings expand our understanding of the favorable influence of socioemotional context on Hot inhibitory control during adolescence in healthy individuals.